(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article is devoted to the analysis of the principles of justice in the regulation of contractual relations and liability of the parties in civil law. The evolution of civil law is considered, with an emphasis on the transition from liberal-individualistic to socialized approaches, which is due to the need to protect weak parties in contractual relations. In the context of freedom of contract, which remains the main principle, the author identifies the risks of dominance of strong parties and suggests using justice mechanisms to restore balance. International experience and practice of applying the principle of justice in the legal systems of different countries, including the Republic of Uzbekistan, are also examined. The article suggests ways to improve legal mechanisms and judicial control to ensure justice in contractual relations.